A Canvas of Similes: Unveiling Thematic Richness in Graham Greene's “The Power and The Glory” - Zulfikri, Zulfikri; Mansur, Nurfauziah; Rengur, Zul Aini (Datokarama English Education Journal, 2023)
This research delves into the profound narrative artistry of Graham Greene's "The Power and The Glory" by analyzing 10 selected similes representing five types based on XuoGuo's classification. The simile types include Descriptive, Illuminative, Illustrative, Open, and Closed Similes, each contributing uniquely to the novel's thematic tapestry. Utilizing a qualitative method, the research systematically categorizes and scrutinizes similes, identifying prevalent types, and unraveling their patterns and thematic implications. Descriptive similes, comparing a shark's fin to a periscope, enhance vivid imagery and introduce concealed dangers. Illuminative similes, equating knowledge to a dark explicable spot in an X-ray photograph, provide nuanced insights into character understanding and thematic depth. Illustrative similes, likening a gold bangle to a padlock, introduce visual metaphors and layers of meaning. Open similes, like having golden shoes, infuse imaginative qualities into actions, while closed similes, comparing a man to Prometheus, draw explicit parallels, enriching characterizations with mythological undertones. This research identifies a total of 47 similes within the novel. By shedding light on the intricate use of similes in "The Power and The Glory," this research contributes significantly to understanding Greene's stylistic choices, serving as a valuable resource for scholars, literary enthusiasts, and those exploring the depths of figurative language in Greene's masterful storytelling.